Evaluation of magnetic resonance sialography and ultrasonography findings in salivary glands of patients with xerostomia - Mahrokh Imanimoghaddam (Cumhuriyet University, 2016)
Objectives: The aim of the study was to assess MR sialography and Ultrasonography asobjective tools to examine salivary glands in patients with xerostomia.Materials and Methods: In this Cross-sectional descriptive study, MR sialography using salivarysecretion stimulation was performed in 16 patients (with the chief complaint of xerostomia) and11 healthy volunteers. Visibility of the main duct and ductal branches were evaluated before andafter stimulation in axial and oblique sagittal plans, and were classified in to three grades (poor,fair & good). Patients and volunteers were also examined by ultrasonography; their parenchymalhomogeneity of the salivary glands was graded from 0 to 5 and their echogenicity was dividedto three levels: hypoecho, isoecho and hyperecho. Size of the salivary glands was also measured.Dependent T-test and independent T-test,Spearman and Chi-square analysis were performed toanalyze the results.Results: In this study the results showed no significant difference in the visibility of salivaryglands ducts before and after salivary secretion stimulation in healthy volunteers. In thepatients group, however, significant difference was seen in the visibility of salivary glands ductsafter stimulation in sagittal planes of right and left parotid glands (P-Value=0.033) as well asleft submandibular glands (P-Value=0.035). No significant difference in the visibility of salivaryglands ducts was observed between healthy volunteers and patients,except in sagittal plan of leftparotid glands (P-Value=0.004). In addition, there was no significant difference in parenchymalcharacteristics and size of salivary glands in ultrasonography results in the two groups. NoSignificant correlation could be established between MR Sialography and Ultrasonographyfindings.Conclusions: Achieving no significant difference in imaging results between patients andvolunteers suggests that MR sialographic images and US features may not serve as suitablediagnostic criteria in patients with xerostomia.